Kotovska O.P. Continental tradition of public policy and current challenges to the European Union - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The article reveals the continental tradition of public policy in historical peculiarities of its formation and argues the challenges, which the EU faces in the last few years. The historical context of the usage of the term “public policy” is shown in comparison with the Anglo-Saxon tradition, since public policy as a separate scienti c discipline arose in the 1950s in the United States.